Quantifying β-catenin subcellular dynamics and cyclin D1 mRNA transcription during Wnt signaling in single living cells - Pinhas Kafri; Sarah E Hasenson; Itamar Kanter; Jonathan Sheinberger; Noa Kinor; Sharon Yunger; Yaron Shav-Tal (eLife, 2016)
Signal propagation from the cell membrane to a promoter can induce gene expression. To examine signal transmission through sub-cellular compartments and its effect on transcription levels in individual cells within a population, we used the Wnt/β-catenin signaling pathway as a model system. Wnt signaling orchestrates a response through nuclear accumulation of β-catenin in the cell population. However, quantitative live-cell measurements in individual cells showed variability in nuclear β-catenin accumulation, which could occur in two waves, followed by slow clearance. Nuclear accumulation dynamics were initially rapid, cell cycle independent and differed substantially from LiCl stimulation, presumed to mimic Wnt signaling. β-catenin levels increased simultaneously at adherens junctions and the centrosome, and a membrane-centrosome transport system was revealed. Correlating β-catenin nuclear dynamics to cyclin D1 transcriptional activation showed that the nuclear accumulation rate of change of the signaling factor, and not actual protein levels, correlated with the transcriptional output of the pathway.